On the willingness to exit street hawking - Adusei Jumah; Ernest Somua-Wiafe; Barnabas Apom (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2021)
This paper uses a generalized estimating equations approach to investigate the willingness of street hawkers in Accra to exit their trade when offered viable alternatives. We observe a direct relationship between willingness to exit hawking and age. Willingness to exit hawking declines over increasing experience. Hawkers who have encountered arrest are less likely to exit. Also, hawkers who received financial assistance to facilitate their business are less likely to exit. Plus, monthly savings from hawking may indirectly influence a rejection of the offer to start an alternative trade. Finally, the willingness to quit hawking is not significantly influenced by gender, sales revenue, and the road description in the model. The results of the analysis could help improve the success of future intervention programmes.
Keywords: C35; E26; 330; street hawking; GEE; logit; willingness to exit